Overview of the Research and Innovation Sector in the Western Balkans - World Bank (Washington, DC, 2014)
This overview of the research sector in the Western Balkans is a companion piece to the Western Balkans regional research and development (R and D) strategy for innovation. The strategy aims to strengthen the region's research capacity, enhance intraregional cooperation, promote collaboration with business sectors, explore possibilities for financing R and D from European Union (EU) funding schemes and other external sources, and help integrate the region into the European research area (ERA) and innovation union. This overview provides the background and analysis that informed the development of the strategy. The background work includes four studies on the different components of the research sector, a policy questionnaire, and seven country studies reviewing key policies, institutions, and performance of the national research sectors. This overview outlines the performance of the research and innovation sector, and describes the major drivers of this performance. It starts by presenting a framework of the different components of research and innovation in the Western Balkans. This leads into section two discussing the performance of the research sector, which has been improving, but still lags international benchmarks. This reflects a number of challenges facing the sector, including the effects of a substantial brain drain, insufficient funding and a mismatch between research facilities, and economic needs. Section three discusses the technology transfer system and its important role in the performance of the research and innovation sector as a whole. The contribution of technology transfer in the region is limited, as reflected for example, in the limited interaction between the research and enterprise sectors. The enterprise sector is discussed in section four. Section five describes the policy and institutional framework, pointing out a number of areas where this can be strengthened. This includes improving the career path for researchers, providing more funding through competitive processes as opposed to block grants, and continuing to strengthen policy co-ordination. The final section concludes.